Modelling the surface of amorphous dehydroxylated silica: the influence of the potential on the nature and density of defects. (3rd January 2018) - Halbert, Stéphanie; Ispas, Simona; Raynaud, Christophe; Eisenstein, Odile
Abstract : The nature and density of defects on the amorphous dehydroxylated silica surface are studied by molecular dynamics for information on the silanol groups of pretreated silica. Abstract : Molecular dynamics (MD) calculations using two effective pair potentials BKS and CHIK have been carried out to represent the structures of the amorphous dehydroxylated silica surface in liquid (3400 and 2500 K) and glassy (1000 and 300 K) states. Previous studies have shown that CHIK performs better to represent the properties of bulk silica and this may result from the different values of the Si–O and O–O parameters, as well as from an additional Si⋯Si short range interaction term. The two potentials show similar trends in the change of structures upon going from the internal to the surface parts of the samples. However, the additional flexibility, likely due to the presence of the Si⋯Si short range interaction, relative to BKS, results in a surface which has overall more defects like in particular small 2-membered rings (SiO2 )2 and dangling Si–O bonds. This cumulated density of defects corresponds qualitatively to the density of functionalized Si–OH obtained experimentally. This study shows that CHIK gives a good representation of the silica surface.